2016
DOI: 10.1161/jaha.115.002850
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease Is a Predictor of Progression to Dialysis in Patients With Chronic Kidney Disease, Type 2 Diabetes Mellitus, and Anemia: An Analysis of the Trial to Reduce Cardiovascular Events With Aranesp Therapy (TREAT)

Abstract: BackgroundAlthough clear evidence shows that chronic kidney disease is a predictor of cardiovascular events, death, and accelerated coronary artery disease (CAD) progression, it remains unknown whether CAD is a predictor of progression of chronic kidney disease to end‐stage renal disease. We sought to assess whether CAD adds prognostic information to established predictors of progression to dialysis in patients with chronic kidney disease, diabetes, and anemia.Methods and ResultsUsing the previously described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…Sabe et al also found that CAD was independently associated with death in TREAT study participants 7. Study of prevalent cohorts of Medicare enrollees from 1996 to 2000 showed that those with CKD are 5 to 10 times more likely to die before reaching ESRD than the non‐CKD group 15.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Sabe et al also found that CAD was independently associated with death in TREAT study participants 7. Study of prevalent cohorts of Medicare enrollees from 1996 to 2000 showed that those with CKD are 5 to 10 times more likely to die before reaching ESRD than the non‐CKD group 15.…”
mentioning
confidence: 95%
“…6 In the present study, Sabe et al noted that those with CAD were less likely to have proteinuria, but the eGFR was not significantly different between those with and without CAD, which could not be explained by use of angiotensin-converting enzyme inhibitor or angiotensin receptor blockers. 7 Traditionally, diabetic nephropathy is described as a chronic progressive disorder that is characterized by microalbuminuria, followed by macroalbuminuria, and hypertension leading to progressive loss of eGFR resulting in ESRD. Recently, several epidemiological studies have shown that frequently T2DM patients with reduced eGFR have no proteinuria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Main topics were the investigation of diabetic patients [8][9][10] and optimized dosage of erythropoietin. 2,[11][12][13] Last but not least, it is important to note that Peter has held numerous positions in national and international societies reflecting again his conviction to promote mutual international understanding and involvement of the global dialysis industry. The International Society for Artificial Organs (ISAO) elected him Secretary General of the 5th World Congress in 1985 and Secretary Treasurer in 1990.…”
Section: N M E M O R I a Mmentioning
confidence: 99%
“…In order to promote high quality treatment options together with patient satisfaction, Peter’s interest and curiosity further stimulated him to be involved in clinical trials even after his formal retirement from his position as professor in medicine at Northwestern University in Chicago. Main topics were the investigation of diabetic patients and optimized dosage of erythropoietin …”
mentioning
confidence: 99%